Prostor v slovenski zgodovinski povesti in njegova geografska prezentacija - Hladnik, Miran (Slavistična revija, 2012)
Historical tales are predominantly situated in geographically determinate spaces that can be cartographically represented on maps. Such illustrative maps are very valuable tools of communication. Analyzing data and presenting them on the maps by using geographic information systems requires data first to be organized in tables. Data compilation for Slovene historical novels from1999 also contains data on setting. Data for forty-eight novels selected out the 310 recorded in this compilation were amended and standardized for trial presentation on web maps. This article presents experiences and dilemmas when specifying setting in novels. It also explains data preparation for a new data compilation and their presentation in maps. It ties them to the previous findings about spatial characteristics and its role in this genre.Presentation of other literary data on the maps is also discussed.
Keywords: GIS; historical novel; literarna geografija; literarna kartografija; literary cartography; literary geography; Slovene literature; slovenska književnost; zgodovinska povest; zgodovinski roman